2007
DOI: 10.1007/s10800-007-9310-8
|View full text |Cite
|
Sign up to set email alerts
|

The corrosion and electrochemical behaviour of pure aluminium in alkaline methanol solutions

Abstract: The corrosion and electrochemical behaviour of pure aluminium in alkaline methanol solutions has been investigated. The results of hydrogen collection experiments showed that aluminium has a lower corrosion rate in alkaline methanol solutions compared to water based solutions and that the corrosion rate increases with increasing water content of the solution. Polarization and galvanostatic discharge experiments showed that there is a wide potential window of electrochemical activity and a better discharge perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…Alcohols used to form both aqueous and non-aqueous alkaline KOH solutions for aluminium corrosion tests include methanol [162,163], ethanol [164] and propanol [165]. Without any water, there was no hydrogen evolution from the surface of the aluminium in these alkaline alcohol solutions.…”
Section: Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohols used to form both aqueous and non-aqueous alkaline KOH solutions for aluminium corrosion tests include methanol [162,163], ethanol [164] and propanol [165]. Without any water, there was no hydrogen evolution from the surface of the aluminium in these alkaline alcohol solutions.…”
Section: Alcoholsmentioning
confidence: 99%
“…The open-circuit corrosion current density was extremely low at 0.0976 mA cm À2 in a 4 mol dm À3 KOH solution at 25 C [164]. These solutions almost completely inhibited the oxidation of aluminium as replacing water with the other solvents decreases the ionic conductivity of the electrolyte and the hydration of the surface product layer [161,162]. The rate of oxidation of the aluminium was improved upon mixing the alkaline alcohol solutions with water, although still inferior to the performance in a 100% aqueous solution.…”
Section: Alcoholsmentioning
confidence: 99%
“…When immersed in an alkaline medium containing KOH or NaOH, aluminum can suffer anodic dissolution releasing AlO -and Al(OH) -4 ions. This aluminum species tends to form a passive layer of Al(OH) 3 85 through the reduction of electrolytes such as water, 86 or methanol, 87 causing hydrogen evolution in the process. 87,88 The exposure of different metals to biodiesel and the presence of dissolved oxygen can increase the corrosivity of the fuel.…”
Section: Metallic Corrosion Mechanisms and The Formation Of Corrosionmentioning
confidence: 99%
“…This aluminum species tends to form a passive layer of Al(OH) 3 85 through the reduction of electrolytes such as water, 86 or methanol, 87 causing hydrogen evolution in the process. 87,88 The exposure of different metals to biodiesel and the presence of dissolved oxygen can increase the corrosivity of the fuel. Different factors may be involved in the corrosion processes in biodiesel, such as changes in the acid values, increases in water content, the presence of oxidation products, the presence of metal species and changes in the structural characteristics of the biodiesel.…”
Section: Metallic Corrosion Mechanisms and The Formation Of Corrosionmentioning
confidence: 99%
“…It has been reported that anodic dissolution of aluminium in the alkaline medium takes place through a stepwise addition of surface hydroxyl species, culminating in the chemical dissolution of Al (OH) 3 in the presence of surface oxide film. The overall anodic reaction taking place in the corrosion of aluminium in the alkaline solution is represented as under [22][23][24][25] …”
Section: Potentiodynamic Polarization Studymentioning
confidence: 99%